Phospholipids and sports performance - Purpura Martin; Jäger Ralf; Kingsley Michael (Taylor & Francis Group, 2007)
Abstract Phospholipids are essential components of all biological membranes. Phosphatidylcholine (PC) and Phosphatidylserine (PS) are Phosphatidyl-phospholipids that are required for normal cellular structure and function. The participation in physical activity often challenges a variety of physiological systems; consequently, the ability to maintain normal cellular function during activity can determine sporting performance. The participation in prolonged intense exercise has been shown to reduce circulatory choline concentrations in some individuals. As choline is a pre-cursor to the neurotransmitter Acetylcholine, this finding has encouraged researchers to investigate the hypothesis that supplementation with PC (or choline salts) could enhance sporting performance. Although the available data that evaluates the effects of PC supplementation on performance are equivocal, acute oral supplementation with PC (~0.2 g PC per kg body mass) has been demonstrated to improve performance in a variety of sporting activities where exercise has depleted circulatory choline concentrations. Short term oral supplementation with soy-derived PS (S-PS) has been reported to attenuate circulating cortisol concentrations, improve perceived well-being, and reduce perceived muscle soreness after exercise. More recently, short term oral supplementation (750 mg per day of S-PS for 10 days) has been demonstrated to improve exercise capacity during high intensity cycling and tended to increase performance during intermittent running. Although more research is warranted to determine minimum dietary Phospholipid requirements for optimal sporting performance, these findings suggest that some participants might benefit from dietary interventions that increase the intakes of PC and PS.